Neuromuscular Taping Decompression Technique in Diabetic Painful Polyneuropathy: Impact onÃ‚Â PainÃ‚Â Intensity - Harun Muchsin, Achmad; Blow, David; Goysal, Yudy; Wuysang, Audry Devisanty; Tammasse, Jumraini; Bahar, Ashari; Zainuddin, Andi Alfian; Walenna, Nirwana Fitriani (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Background: This study aimed to evaluate the effects of neuromuscular taping decompression technique (NMT) on modifying pain scale in diabetic patients with painful distal symmetrical polyneuropathy (DSPN) at Wahidin Sudirohusodo Hospital, Makassar, Indonesia. Using a pure experimental design with a pre-test and post-test control group method, 30 patients were included: 15 in the treatment group and 15 in the control group. The treatment group received decompression NMT on the dorsal and plantar aspects of the foot twice a week for four weeks, along with vitamin B complex supplementation. The control group received only vitamin B complex. Result: The Mann-Whitney test showed significant improvement (p <0.05) in the pain scale of the treatment group on day 28, with the Numeric Pain Rating Scale (NPRS) score being lower than that of the control group. Conclusion: This study demonstrated the significant pain-reducing effect of NMT in DSPN patients. The combination of vitamin B1, B6, and B12 supplementation with 8 NMT sessions over 28 days reduced pain to 0 on the NPRS scale. Treatment twice a week for 4 weeks, alongside vitamin B, led to near-zero pain, with pain-free results expected after 5 treatments over 17 days. NMT combined with vitamin B reduced pain approximately 2 times faster than vitamin B alone. Keywords: Diabetic Painful Distal Symmetrical Polyneuropathy, DSPN, Diabetic Neuropathic Pain, Neuromuscular Taping, NMT